Pengaruh Intellectual Capital, Cash Holding dan Pertumbuhan Penjualan terhadap Nilai Perusahaan - Trissa Zahrotul Hayat; Indawati, Indawati (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
Company value has an important role as an indicator of shareholder performance and wealth. So this study aims to examine and analyze the effect of Intellectual Capital, Cash Holding and Sales Growth on company value. Performance in industrial companies listed on the Indonesia Stock Exchange for the period 2018 to 2022. This type of research is quantitative research, using secondary data. The data analysis method used is a panel data regression test using the Microsoft Excel and Eviews 12 applications. The population in this study is all industrial sectors listed on the Indonesia Stock Exchange in the period 2018 to 2022. The data collection technique in this study was a purposive sampling technique with the results of the 55 study populations became 14 research samples processed in this study. The results of the study show that Intellectual Capital, Cash Holding and Sales Growth did not simultaneously influence Company Value in industrial companies for the period 2018 to 2022. While partially Intellectual Capital did not influences Company Value, Cash Holding did not effect on Company Value and Sales Growth did effect Value Company.